ESTIMASI KEPADATAN ULAT API MELALUI METODE SAMPLING JARAK - Cukri Rahmi Niani (Universitas Teuku Umar, 2017)
Many types of pests which is found in oil palm plantations such as rats, bees and the caterpillars. Caterpillar and the bagworm, including a caterpillar eaters leaves oil palm plantations. This Research focuses on a caterpillar type Setora nitens at oil palm plantations Karya Tanah Subur in West Aceh. Many ways that has been done to overcome pests caterpillar in oil palm plantations from early monitoring and extermination caterpillar. To know the density caterpillar can be done by counting directly individual caterpillar or with other methods that in this research, the density caterpillar in the estimation through distance sampling techniques. Distance sampling is one of the methods used to estimate the density and the spread population. The sampling distance, a series point or lines are placed randomly on the districts census and measured the distance between individuals who were detected in handcuffs or this point. Ordered Distance, Point Quarter and Variable Area Transect the distance sampling method that used in the research. Based on the explanation, an extensive microinsurance is focused on the estimation density caterpillar using the distance sampling methods.Keywords: Setora nitens, Distance Sampling, Order Distance, Point Quarter, VariableArea Transect.